Ionic liquid catalyst and its preparation method
By using ionic liquid catalysts with decolorizer and degradation agent on the carrier nickel ferrite during the fiber cloth recycling process, the dye removal problem in fiber cloth recycling is solved, and a more efficient plastic recycling and degradation effect is achieved.
Patent Information
- Application Number
- CN202111563362.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-01
- Filing Date
- 2021-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-12-20
AI Technical Summary
The prior art is difficult to effectively remove dyes during the recycling process of fiber cloth, which affects subsequent purification treatment and plastic recycling efficiency.
An ionic liquid catalyst is used based on the carrier nickel ferrite, a carrier surface graft decolorizer (such as carbon material) and a degrading agent (such as a pyrimidine compound) to enhance the decolorization and degradation effect.
Through grafting decolorizer and degradation agent, the decolorization effect of the fiber cloth and the degradation efficiency of the plastic are significantly improved, and more efficient plastic recycling is achieved.
Smart Images

Figure CN115920959B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an ionic liquid catalyst and a preparation method thereof, and in particular to an ionic liquid catalyst with decolorization and degradation effects and a preparation method thereof. Background Art
[0002] With the rise of awareness, how to recycle and reuse industrial and domestic waste has become an important issue and business opportunity today. Among the many domestic wastes, polyethylene terephthalate (PET) plastic products are the largest.
[0003] In order to reduce the amount of plastic waste, people in the relevant technical field are committed to developing closed-loop chemical recycling technologies, such as solvent-assisted chemical degradation, biotechnology degradation or microwave-assisted chemical degradation. Closed-loop chemical recycling technology focuses on the sustainability of the supply chain, hoping to manufacture products without generating unrecyclable waste in order to cope with the rising population and dwindling resources.
[0004] Among various recyclable plastic products, fiber cloth obviously has a place. In the recycling process of fiber cloth, how to effectively remove the dye is an important issue. If the dye cannot be completely removed, the fiber cloth will not be able to undergo subsequent purification treatment.
[0005] In order to remove the dye on the fiber cloth, an extraction solvent and a catalyst are generally added to perform extraction. The prior art also provides many documents on how to improve the extraction effect, such as selecting a specific solvent or using a specific extraction method.
[0006] After the decolorization process, the fiber cloth can be subjected to a degradation process to obtain a monomer mixture. Then, the impurities or impurities in the monomer mixture are removed to achieve a purification effect, and the purified monomer mixture is polymerized again to obtain recycled PET. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide an ionic liquid catalyst and a preparation method thereof in view of the deficiencies of the prior art.
[0008] In order to solve the above technical problems, one of the technical solutions adopted by the present invention is to provide an ionic liquid catalyst. The ionic liquid catalyst includes a carrier, the components of the carrier include nickel ferrite, and an outer surface of the carrier is modified with a decolorizing agent and a degradation agent; wherein the decolorizing agent is grafted onto the nickel atoms of the carrier, and the degradation agent is grafted onto the iron atoms of the carrier.
[0009] Preferably, the decolorizing agent is composed of carbon material.
[0010] Preferably, the weight ratio of the carbon material to the carrier is 0.01 to 0.05.
[0011] Preferably, the decolorizing agent is a solid carbon fiber tube.
[0012] Preferably, the degradation agent comprises an ionic liquid.
[0013] Preferably, the weight ratio of the ionic liquid to the carrier is 2 to 4.5.
[0014] Preferably, the ionic liquid is a pyrimidine compound, a pyridine compound, a pyrazole compound, a piperidine compound, an imidazole compound or a combination thereof.
[0015] Preferably, the degradation agent is linked to the iron atom of the carrier via a bridging structure.
[0016] Preferably, the size of the carrier is less than or equal to 100 nanometers.
[0017] In order to solve the above technical problems, another technical solution adopted by the present invention is to provide a method for preparing an ionic liquid catalyst. The method for preparing the ionic liquid catalyst includes the following steps: providing a carrier, the components of the carrier include nickel ferrite; surface modifying the carrier so that a decolorizing agent is grafted onto the nickel atoms of the carrier, and a degradation agent is grafted onto the iron atoms of the carrier, so as to obtain an ionic liquid catalyst.
[0018] Preferably, the decolorizing agent is first grafted onto the nickel atom of the carrier to obtain a composite powder material, and then the degradation agent is grafted onto the iron atom of the carrier to obtain the ionic liquid catalyst.
[0019] Preferably, the decolorizing agent is composed of carbon material.
[0020] Preferably, the step of grafting the decolorizing agent includes: introducing carbon dioxide at a temperature of 400° C. to 800° C., reducing the carbon dioxide and grafting it onto the nickel atoms of the carrier to obtain a composite powder material.
[0021] Preferably, the composite powder material is heat treated at a temperature of 500°C to 800°C.
[0022] Preferably, the degradation agent comprises an ionic liquid.
[0023] Preferably, a siloxane is grafted onto the iron atom of the carrier to form a bridging structure, and then the ionic liquid is reacted with the bridging structure so that the ionic liquid is grafted onto the iron atom of the carrier through the bridging structure.
[0024] Preferably, the ionic liquid first reacts with a siloxane to form an intermediate, and then the intermediate reacts with the carrier, so that the ionic liquid is grafted onto the iron atom of the carrier through the siloxane.
[0025] One of the beneficial effects of the present invention is that the ionic liquid catalyst and its preparation method provided by the present invention can achieve the effect of improving the decolorization effect and degradation effect through the technical scheme of "grafting the decolorizing agent onto the nickel atom of the carrier" and "grafting the degradation agent onto the iron atom of the carrier".
[0026] To further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the drawings provided are only for reference and description and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the ionic liquid catalyst of the present invention.
[0028] Figure 2 The figure is a flow chart of the preparation method of the ionic liquid catalyst of the present invention.
[0029] Figure 3 FIG. 1 is a reaction flow chart of step S2 in the method for preparing the ionic liquid catalyst of the present invention.
[0030] Figure 4 This is a scanning electron microscope photograph of the carrier and the decolorizing agent in step S3.
[0031] Figure 5 for Figure 4 A magnified view of a local area.
[0032] Figure 6 for Figure 5 A magnified view of a local area.
[0033] Fig. 7A , 7B FIG. 1 is a reaction flow chart of step S3 in the method for preparing the ionic liquid catalyst of the present invention. DETAILED DESCRIPTION
[0034] The following is an explanation of the implementation methods of the "ionic liquid catalyst and its preparation method" disclosed in the present invention through specific examples. Those skilled in the art can understand the advantages and effects of the present invention from the contents disclosed in this specification. The present invention can be implemented or applied through other different specific embodiments, and the details in this specification can also be modified and changed in various ways based on different viewpoints and applications without departing from the concept of the present invention. In addition, the drawings of the present invention are only simple schematic illustrations and are not depicted according to actual dimensions. It is stated in advance. The following implementation methods will further explain the relevant technical contents of the present invention in detail, but the disclosed contents are not intended to limit the scope of protection of the present invention. In addition, the term "or" used in this article may include any one or more combinations of the associated listed items depending on the actual situation.
[0035] The present invention provides an ionic liquid catalyst, which has both decolorization and degradation effects. Therefore, the ionic liquid catalyst of the present invention is particularly suitable for treating waste plastic fabrics. Due to the decolorization and degradation effects, when treating waste plastic fabrics, a relatively simple process can be used to achieve the effect of recycling waste plastic fabrics.
[0036] See also Figure 1 As shown, the ionic liquid catalyst of the present invention comprises a carrier 10, and an outer surface 100 of the carrier 10 is grafted with a decolorizing agent 20 and a degradation agent 30. Therefore, the ionic liquid catalyst of the present invention has the function of improving the decolorizing effect and the degradation effect.
[0037] The carrier 10 includes nickel ferrite (NiFe2O4). The shape of the carrier 10 can be spherical or other irregular shapes, and the shape of the carrier 10 can be adjusted according to different requirements (eg, surface area). The size of the carrier 10 can be micrometer-level or nanometer-level.
[0038] In a preferred embodiment, the size of the carrier 10 is nanometer-sized. When the carrier 10 is nanometer-sized, the space between the carrier 10 and the degradation agent 30 grafted on the carrier 10 will also be nanometer-sized, and the space can help the adsorption of the dye to enhance the decolorization effect of the ionic liquid catalyst. Accordingly, the nanometer-sized carrier 10 can make the ionic liquid catalyst have a better decolorization effect. Specifically, the size of the carrier 10 is less than or equal to 500 nanometers. Preferably, the size of the carrier 10 is less than or equal to 300 nanometers. More preferably, the size of the carrier 10 is less than or equal to 200 nanometers. Even more preferably, the size of the carrier 10 is less than or equal to 100 nanometers.
[0039] The decolorizing agent 20 may be grafted onto the outer surface 100 of the carrier 10 by adsorption or bonding. Specifically, the decolorizing agent 20 is grafted onto the nickel atoms of the carrier 10. When the ionic liquid catalyst contacts the waste plastic fabric, the dye on the waste plastic fabric can be adsorbed by the decolorizing agent 20, thereby achieving a decolorizing effect.
[0040] In a preferred embodiment, the decolorizing agent 20 is composed of a carbon material. For example, the carbon material can be graphite, graphene, graphene oxide, carbon nanotubes, carbon black or activated carbon, but the present invention is not limited thereto. Based on the total weight of the carrier 10, the weight ratio of the decolorizing agent 20 to the carrier 10 is 0.01 to 0.05. In addition, the decolorizing agent 20 can be a solid carbon fiber tube made of carbon material, the solid carbon fiber tube extends outward from the outer surface 100 of the carrier 10, and the solid carbon fiber tube is formed by stacking multiple graphite layers in parallel on the outer surface 100 of the carrier 10. The actual structure of the solid carbon fiber tube will be described later.
[0041] In order to achieve a better decolorization effect, the weight ratio of the carbon material to the carrier is 0.01 to 0.04. More preferably, the weight ratio of the carbon material to the carrier 10 is 0.01 to 0.035. Even more preferably, the weight ratio of the carbon material to the carrier 10 is 0.01 to 0.03. However, the present invention is not limited thereto.
[0042] The degradation agent 30 may be grafted onto the outer surface 100 of the carrier 10 by adsorption or bonding. Specifically, the degradation agent 30 is grafted onto the iron atom of the carrier 10. When the ionic liquid catalyst contacts the waste plastic fabric, the degradation agent 30 may help degrade the waste plastic fabric, thereby achieving a degradation effect.
[0043] In a preferred embodiment, the degradation agent 30 includes an ionic liquid. An ionic liquid refers to a liquid ionic compound. An ionic liquid generally has a low melting point and is composed of charged ions and short-lived ion pairs. An ionic liquid can be a positively charged ionic compound or a negatively charged ionic compound. In a preferred embodiment, the ionic liquid is a positively charged ionic compound. Based on the total weight of the carrier 10, the weight ratio of the ionic liquid to the carrier 10 is greater than or equal to 1.8.
[0044] When the ionic liquid is a positively charged ionic compound, the cationic moiety contributing the positive charge may be an imidazolium ion, a pyridinium ion, a quaternary phosphonium ion, a quaternary ammonium ion, a guanidinium ion, a sulfonium ion, a choline ion or a morpholinium ion.
[0045] In a preferred embodiment, the weight ratio of the ionic liquid to the carrier 10 is 2.0 to 4.5. More preferably, the weight ratio of the ionic liquid to the carrier 10 is 2.0 to 4.0. Even more preferably, the weight ratio of the ionic liquid to the carrier 10 is 2.0 to 3.5. However, the present invention is not limited thereto.
[0046] Specifically, the ionic liquid can be an aromatic heterocyclic compound, such as pyrimidine, pyridine, pyrazole, piperidine, imidazole or a combination thereof, but the present invention is not limited thereto.
[0047] In some embodiments, the aromatic heterocyclic compound may have one or more alkyl groups with carbon numbers of 1 to 5. For example, the ionic liquid may be an imidazole compound with one or more alkyl groups with carbon numbers of 1 to 5, such as N-butyl imidazole and 1-butyl-3-methyl imidazole. However, the present invention is not limited thereto, and the type of the ionic liquid may be selected according to the type of material of the waste plastic fabric.
[0048] In some embodiments, the ionic liquid catalyst may further include a bridging structure 40, and the degradation agent 30 may be grafted onto the outer surface 100 of the carrier 10 through the bridging structure 40. One end of the bridging structure 40 is connected to the iron atom of the carrier 10, and the other end is connected to the ionic liquid, so that the ionic liquid can be grafted onto the iron atom of the carrier 10.
[0049] In some embodiments, the bridging structure 40 is formed by a low molecular weight siloxane, and the average weight molecular weight of the bridging structure 40 is 100 g / mol to 500 g / mol. Preferably, the average weight molecular weight of the bridging structure 40 is 100 g / mol to 300 g / mol. Specifically, the bridging structure 40 is formed by a halogen-containing siloxane, and the degradation agent 30 is connected to the iron atom of the carrier 10 through the halogen-containing siloxane. For example, the bridging structure 40 can be formed by a chlorine-containing siloxane, or the bridging structure 40 can also be formed by a bromine-containing siloxane.
[0050] In some preferred embodiments, the bridging structure 40 is formed by a low carbon number chlorinated siloxane, which can be represented by formula (I), where R 1 , R 2 and R 3 Each is independently an alkyl group having 1 to 4 carbon atoms. The low carbon bromine-containing siloxane can be represented by formula (II), wherein R 1 , R 2 and R 3 Each is independently an alkyl group having a carbon number of 1 to 4. However, the present invention is not limited thereto.
[0051]
[0052] The method for preparing the ionic liquid catalyst of the present invention comprises the following steps: providing a carrier 10, wherein the components of the carrier 10 include nickel ferrite; modifying the carrier 10 so that the nickel atoms of the carrier 10 are grafted with a decolorizing agent, and the iron atoms of the carrier 10 are grafted with a degradation agent 30.
[0053] In the present invention, the order of grafting the decolorizing agent 20 and the grafting the degradation agent 30 is not limited. That is, the decolorizing agent 20 can be grafted onto the carrier 10 first, and then the degradation agent 30 can be grafted onto the carrier 10; or the degradation agent 30 can be grafted onto the carrier 10 first, and then the decolorizing agent 20 can be grafted onto the carrier 10. In a preferred embodiment, the decolorizing agent 20 is grafted onto the carrier 10 first, and then the degradation agent 30 is grafted onto the carrier 10.
[0054] See also Figure 2 As shown, the method for preparing the ionic liquid catalyst of the present invention comprises the following steps: providing a carrier (step S1), wherein the components of the carrier include nickel ferrite. Grafting a decolorizing agent onto the nickel atoms of the carrier to obtain a composite powder material (step S2). Grafting a degradation agent onto the iron atoms of the carrier to obtain an ionic liquid catalyst (step S3).
[0055] See also Figure 3 As shown, Figure 3 The reaction flow chart in step S2 is shown. In step S2, in order to graft the decolorizing agent onto the carrier, the present invention uses carbon dioxide as a raw material and reduces and deposits the carbon dioxide on the carrier to graft the decolorizing agent onto the carrier.
[0056] Specifically, the present invention uses a fixed bed reactor reduction method to react carbon dioxide with a carrier at a temperature of 400°C to 800°C for 2 to 36 hours. After the carbon dioxide is reduced to carbon material, it will be grafted onto the nickel atoms of the carrier to complete the composite powder material (C: NiFe2O4). It should be noted that during the above-mentioned carbon dioxide reduction process, the iron atoms on the surface of the carrier may also be reduced to form some hydroxyl groups (such as Figure 3 ).
[0057] After the decolorizing agent is grafted, the composite powder material may be further heat-treated at a temperature of 500° C. to 800° C. for 1 to 2 hours. In this way, the crystal lattice of the composite powder material may be rearranged to have more stable properties.
[0058] See also Figures 4 to 6 As shown, Figures 4 to 6 This is a scanning electron microscope (SEM) image of the composite powder material of the present invention. Figures 4 to 6 It can be seen that the decolorizing agent is grafted on the outer surface of the carrier and extends outward from the outer surface of the carrier to present the appearance of a solid carbon fiber tube. Specifically, the carbon material is a thin layer of structural units, which are stacked parallel to the outer surface of the carrier to form the shape of a solid carbon fiber tube, and the axial direction of the solid carbon fiber tube is perpendicular to the outer surface of the carrier.
[0059] See also Fig. 7A and 7B As shown, Fig. 7A and 7B The reaction flow chart in step S3 is shown. In step S3, the chlorosiloxane (bridging structure) is reduced in an acidic environment (pH = 4-5) and has a hydroxyl group. The reduced chlorosiloxane then reacts with the composite powder material in step 2, and the chlorosiloxane is grafted onto the composite powder material through the hydroxyl group. Specifically, the chlorosiloxane is grafted onto the iron atom of the carrier. Next, N-butylimidazole (ionic liquid) is added in an acidic environment (pH = 4-5), and N-butylimidazole reacts with the chlorine group of the chlorosiloxane and is grafted onto the bridging structure. In this way, the degradation agent can be grafted onto the composite powder material through the bridging structure, and the ionic liquid catalyst of the present invention can be obtained.
[0060] Apart from Fig. 7A and 7B In addition to the schematic reaction flow chart, N-butyl imidazole (ionic liquid) can also be reacted with chlorosiloxane to form an intermediate containing ionic liquid, and then the intermediate is reacted with the composite powder material in step 2. In this way, the degradation agent can also be grafted onto the composite powder material through the bridging structure.
[0061] In order to verify the advantages of the ionic liquid catalyst of the present invention, according to Figure 3 and Fig. 7A and 7B The ionic liquid catalysts of Examples 1 to 4 were prepared according to the reaction process. That is, nickel ferrite was used as a carrier, carbon material reduced by carbon dioxide was used as a decolorizing agent, and ionic liquid connected by a bridging structure was used as a degradation agent. The specific component contents of Examples 1 to 4 are listed in Table 1. In Table 1, the carbon material content ratio refers to the weight ratio of the carbon material to the carrier. When the carbon material content ratio is 0.5%, it means that the weight ratio of the carbon material to the carrier is 0.005.
[0062] Table 1
[0063]
[0064] Next, an appropriate amount of the ionic liquid catalyst in Examples 1 to 4 is added to ethylene glycol and waste PET fiber cloth, and the amount of the ionic liquid catalyst added is 0.2 wt % based on the total weight of the ethylene glycol and the waste PET fiber cloth. Then, the ethylene glycol and the waste PET fiber cloth are heated and stirred at a temperature of 180° C. to decolorize / degrade the ethylene glycol and the waste PET fiber cloth, and a decolorized and degraded monomer mixture is obtained after the reaction. The components of the monomer mixture include bis(hydroxyethyl) terephthalate (BHET), which is a monomer formed after the degradation of polyethylene terephthalate.
[0065] Table 2 lists the time of decolorization / degradation reaction, degradation efficiency and hue value of the monomer mixture. The degradation efficiency refers to the percentage of the molar number of monomers produced by actual degradation divided by the molar number of monomers produced by theoretical degradation.
[0066] Table 2
[0067]
[0068] From the results in Table 1 and Table 2, it can be seen that the ionic liquid catalyst of the present invention can achieve a good decolorization effect through the decolorizing agent (carbon material) on the carrier, and can achieve a good degradation effect through the degradation agent (ionic liquid) on the carrier. In this way, the ionic liquid catalyst of the present invention can simultaneously improve the effects of the decolorization reaction and the degradation reaction.
[0069] Please compare the results of Example 1 with those of Examples 2 to 4. When the carbon material content ratio is greater than 0.5%, the degraded monomer mixture may have a whiter hue and meet certain appearance standards. Specifically, after decolorization, the L value of the monomer mixture is greater than 80%, the a value is between 1 and -1, and the b value is between 6.5 and -6.5.
[0070] In the present invention, the weight ratio of the carbon material to the carrier is greater than 0.005 to 0.05. Preferably, the weight ratio of the carbon material to the carrier is 0.01 to 0.04. More preferably, the weight ratio of the carbon material to the carrier is 0.01 to 0.035.
[0071] Please compare the results of Example 3 with those of Example 4. When the weight ratio of the ionic liquid addition amount to the carrier is greater than 2.8 (preferably, the weight ratio of the ionic liquid addition amount to the carrier is 3.0 to 4.0), a higher degradation efficiency can be achieved in a shorter reaction time.
[0072] In a preferred embodiment, the weight ratio of the ionic liquid to the carrier is greater than 2.8 to 4.5. More preferably, the weight ratio of the ionic liquid to the carrier is 3.0 to 4.0. Even more preferably, the weight ratio of the ionic liquid to the carrier is 3.2 to 3.5.
[0073] Please compare the results of Example 2 and Example 3. When the weight ratio of the carbon material to the carrier is higher, the degradation rate of the ionic liquid catalyst will slightly decrease. It can be seen that the present invention simultaneously controls the weight ratio of the carbon material to the carrier and the weight ratio of the ionic liquid to the carrier, so that the ionic liquid catalyst can have good decolorization and degradation effects.
[0074] In a preferred embodiment, the weight ratio of the carbon material to the carrier is greater than 0.005, and the weight ratio of the ionic liquid to the carrier is greater than or equal to 2.8. Preferably, the weight ratio of the carbon material to the carrier is greater than 0.008, and the weight ratio of the ionic liquid to the carrier is greater than or equal to 2.9.
[0075] [Beneficial Effects of Embodiments]
[0076] One of the beneficial effects of the present invention is that the ionic liquid catalyst and its preparation method provided by the present invention can achieve the effect of improving the decolorization effect and degradation effect through the technical scheme of "grafting the decolorizing agent onto the nickel atom of the carrier" and "grafting the degradation agent onto the iron atom of the carrier".
[0077] Furthermore, through the technical solution of "the weight ratio of the carbon material to the carrier is 0.01 to 0.05", the ionic liquid catalyst of the present invention can have a better decolorization effect.
[0078] Furthermore, through the technical solution of "the weight ratio of the ionic liquid to the carrier is 2 to 4.5", the ionic liquid catalyst of the present invention can have a better degradation effect.
[0079] Furthermore, through the technical solution of "the size of the carrier is less than or equal to 100 nanometers", the ionic liquid catalyst of the present invention can have a better decolorization effect.
[0080] The contents disclosed above are only preferred feasible embodiments of the present invention, and are not intended to limit the protection scope of the claims of the present invention. Therefore, all equivalent technical changes made using the contents of the present invention description and drawings are included in the protection scope of the claims of the present invention.
Claims
1. An ionic liquid catalyst, characterized in that: The ionic liquid catalyst comprises: a carrier, the components of the carrier include nickel ferrite, an outer surface of the carrier is modified with a decolorizing agent and a degradation agent; wherein the decolorizing agent is a solid carbon fiber tube, the decolorizing agent is stacked in parallel on the outer surface of the carrier and is formed by extending outward from the outer surface of the carrier, the decolorizing agent is grafted on the nickel atoms of the carrier, and the degradation agent is grafted on the iron atoms of the carrier; The weight ratio of the solid carbon fiber tube to the carrier is 0.01 to 0.05; the degradation agent includes an ionic liquid, and the weight ratio of the ionic liquid to the carrier is 2 to 4.
5.
2. The ionic liquid catalyst according to claim 1, characterized in that The ionic liquid is a pyrimidine compound, a pyridine compound, a pyrazole compound, a piperidine compound, an imidazole compound or a combination thereof.
3. The ionic liquid catalyst according to claim 1, characterized in that The degradation agent is connected to the iron atom of the carrier through a bridging structure.
4. The ionic liquid catalyst according to claim 1, characterized in that The size of the carrier is less than or equal to 100 nanometers.
5. A method for preparing an ionic liquid catalyst, characterized in that: The preparation method comprises: providing a carrier, wherein the carrier comprises nickel ferrite; and The carrier is surface modified so that a decolorizing agent is stacked in parallel on the outer surface of the carrier and extends outward from the outer surface of the carrier to be grafted onto the nickel atom of the carrier, and a degradation agent is grafted onto the iron atom of the carrier to obtain the ionic liquid catalyst, wherein the decolorizing agent is a solid carbon fiber tube; The weight ratio of the solid carbon fiber tube to the carrier is 0.01 to 0.05; the degradation agent includes an ionic liquid, and the weight ratio of the ionic liquid to the carrier is 2 to 4.
5.
6. The method according to claim 5, characterized in that: The decolorizing agent is firstly grafted onto the nickel atom of the carrier to obtain a composite powder material, and then the degradation agent is grafted onto the iron atom of the carrier to obtain the ionic liquid catalyst.
7. The method according to claim 5, characterized in that: The step of grafting the decolorizing agent includes: introducing carbon dioxide at a temperature of 400° C. to 800° C., reducing the carbon dioxide and grafting it onto the nickel atoms of the carrier to obtain a composite powder material.
8. The method according to claim 7, characterized in that: The composite powder material is heat-treated at a temperature of 500° C. to 800° C.
9. The method according to claim 8, characterized in that: A siloxane is grafted onto the iron atom of the carrier to form a bridging structure, and then the ionic liquid is reacted with the bridging structure to make the ionic liquid grafted onto the iron atom of the carrier through the bridging structure.
10. The method according to claim 8, characterized in that: The ionic liquid first reacts with a siloxane to form an intermediate, and then the intermediate reacts with the carrier, so that the ionic liquid is grafted onto the iron atom of the carrier through the siloxane.
Citation Information
Patent Citations
Nanocarbon-activated carbon composite
US20090220767A1
Improved Catalyst Complex and Method of Degradation of a Polymer Material
US20180371206A1